2002
DOI: 10.1038/sj.bjc.6600339
|View full text |Cite
|
Sign up to set email alerts
|

Does place of birth influence endogenous hormone levels in Asian-American women?

Abstract: In 1983 -87, we conducted a population-based case -control study of breast cancer in Asian women living in California and Hawaii, in which migration history (a composite of the subject's place of birth, usual residence in Asia (urban/rural), length of time living in the West, and grandparents' place of birth) was associated with a six-fold risk gradient that paralleled the historical differences in incidence rates between the US and Asian countries. This provided the opportunity to determine whether endogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…This suggests a role for a geographic and environmental influences, potentially through diet, on the phenotype of hirsutism. Although studies on the role of migration and endogenous hormone levels suggest that androgen levels are lower in Western-born women than their counterparts born in Asia or Pakistan (15,16), small trials of women with PCOS suggest that diet may influence sex hormonebinding globulin (SHBG) levels and androgen levels (17)(18)(19)(20). One trial of 28 overweight women with PCOS demonstrated that with energy restriction the participants experienced weight loss and increased SHBG levels accompanied by decreased testosterone levels (17).…”
Section: Discussionmentioning
confidence: 96%
“…This suggests a role for a geographic and environmental influences, potentially through diet, on the phenotype of hirsutism. Although studies on the role of migration and endogenous hormone levels suggest that androgen levels are lower in Western-born women than their counterparts born in Asia or Pakistan (15,16), small trials of women with PCOS suggest that diet may influence sex hormonebinding globulin (SHBG) levels and androgen levels (17)(18)(19)(20). One trial of 28 overweight women with PCOS demonstrated that with energy restriction the participants experienced weight loss and increased SHBG levels accompanied by decreased testosterone levels (17).…”
Section: Discussionmentioning
confidence: 96%
“…Most of the etiological studies have used current area of residence as a definition for rural [10,11] and limited studies which have taken early years of life spent [12] or place of the birth [13,14] in rural areas as a definition for "rural." However, current residence is not a good marker for studying the effect of the rural environment on the risk of breast cancer, as exposures in early life may be more important in the development of breast cancer compared to current exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas androgens have been generally lower in pre-and postmenopausal Asian compared with Caucasian women (48), a recent study showed an inverse correlation with increasing westernization in Asian migrants to the West (67). Published data on androgen concentrations in the maternal and fetal circulation, however, are unavailable, although data 5 from a study of Chinese living in Shanghai and Caucasians in Boston on cord androstenedione and testosterone concentrations are forthcoming.…”
Section: Prominent Hypotheses To Explain Prenatal Risk Factorsmentioning
confidence: 99%